IDENTIFIKASI SENYAWA BIOAKTIF DARI BUBUK DAUN CAKAR AYAM (Selaginella spp.) KOMERSIAL DAN EKSTRAKNYA MENGGUNAKAN METODE FTIR - Witoyo, Jatmiko Eko; Utoro, Panggulu Ahmad Ramadhani; Maligan, Jaya Mahar (Jurnal Pangan dan Gizi, 2024)
Increased public awareness of the back-to-nature lifestyle has encouraged using natural materials, especially for health purposes. One of the natural ingredients that attracts attention and has the potential to be developed is  Selaginella spp. leaves, commonly known as "daun cakar ayam" in Indonesia, have been proven beneficial for human health due to their potential bioactivity. However, the profiles of bioactive compounds in “daun cakar ayam” leaves are lacking, unexplored, and poorly documented. This study aims to identify the functional groups of bioactive compounds in “daun cakar ayam”  leaf powder and its extracts in water and methanolic extracts using the Fourier Transform Infrared (FTIR) method. Commercial “daun cakar ayam” was obtained online and evaluated using a Shimadzu IR Spirit-FTIR spectrophotometer. The FTIR spectra results show that “daun cakar ayam” powder and its extract have different infrared absorption patterns in the 400-4000 cm-1 range.  The functional groups identified in “daun cakar ayam” powder and its extracts include O-H stretching, C-H (stretch and stretching), multiple bonding, C-H (bending and aromatic), C=O, N-H, CH2, CH3, C=C aromatic, C-O, C-O-C, C-N stretching, C-O-H, and C-OH aromatic, which indicate the presence of phenolic, flavonoids, tannins, alkaloids, saponin, and triterpenoids compounds. The FTIR method used in this study successfully confirmed the presence of important bioactive compounds in commercial “daun cakar ayam” leaf powder and its extract qualitatively that have the potential to be used as herbal medicine. Quantifying bioactive compounds from “daun cakar ayam” powder and its extracts, as well as further specific bioactivity testing, are required to develop safe and standardized “daun cakar ayam” based herbal products.